2018
DOI: 10.9758/cpn.2018.16.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of Long-acting Injectable and Oral Second-generation Antipsychotics for the Treatment of Schizophrenia: A Systematic Review and Meta-analysis

Abstract: We aimed to compare the efficacy and safety of long-acting injectable (LAI) and oral second-generation antipsychotics (SGAs) in treating schizophrenia by performing a systematic review and meta-analysis. MEDLINE, EMBASE, PsycINFO, CINAHL, and the Cochrane Library, as well as five Korean databases, were systemically searched to identify studies published from 2000 to 16 April 2015, which compared the efficacy and safety of LAI and oral SGAs. Using data from randomized controlled trials (RCTs), meta-analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
(54 reference statements)
0
12
0
1
Order By: Relevance
“…Long-acting antipsychotics are associated with an increased adherence compared to oral antipsychotics [ 69 ], and consequently to a greater exposure to these drugs that in turn could be associated with a greater risk of metabolic side effects. Supporting this hypothesis, it has been reported that, compared to oral SGAs, long-acting injectable SGAs are associated with a greater risk of some adverse events, such as extrapyramidal and prolactin-related symptoms [ 70 , 71 ], and some metabolic disorders, such as changes in LDL cholesterol [ 72 ]. Despite the benefits of long-acting injectable SGAs [ 73 ], it is important to know the metabolic risk associated with these formulations to facilitate the rational use of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Long-acting antipsychotics are associated with an increased adherence compared to oral antipsychotics [ 69 ], and consequently to a greater exposure to these drugs that in turn could be associated with a greater risk of metabolic side effects. Supporting this hypothesis, it has been reported that, compared to oral SGAs, long-acting injectable SGAs are associated with a greater risk of some adverse events, such as extrapyramidal and prolactin-related symptoms [ 70 , 71 ], and some metabolic disorders, such as changes in LDL cholesterol [ 72 ]. Despite the benefits of long-acting injectable SGAs [ 73 ], it is important to know the metabolic risk associated with these formulations to facilitate the rational use of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…11 Compared to oral agents, LA injectable antipsychotics are associated with lower risk of relapse, fewer hospitalizations, and greater retention on therapy. [11][12][13] In addition, one study found that individuals who were nonadherent to oral antipsychotics were less likely to discontinue LA therapy (p ¼ 0.033) compared with patients on oral therapy. 14 Building upon success in these disease states, LA antiretrovirals are currently being developed for the treatment and prevention of HIV infection.…”
mentioning
confidence: 99%
“…2014; Park et al . 2018). Furthermore, no review to date, as far as we know, has incorporated social functioning as a main outcome.…”
Section: Introductionmentioning
confidence: 99%